Effectiveness of educational and lifestyle interventions to prevent paediatric obesity: systematic review and meta‐analyses of randomized and non‐randomized controlled trials. (20th July 2017) - Gori, D.; Guaraldi, F.; Cinocca, S.; Moser, G.; Rucci, P.; Fantini, M. P.
Summary: Objective: This review and meta‐analysis aim at updating a previous meta‐analysis carried out by Waters et al . on the efficacy of interventions aimed at preventing childhood obesity and at identifying predictors of outcome. Methods: Using an ad‐hoc search string, PubMed database was searched for studies assessing body mass index reduction associated with programmes lasting ≥12 weeks in overweight and obese children aged 2–18 years. Studies designed for children with eating disorders or relevant comorbidities were excluded. Studies meeting inclusion criteria were classified according to patient age (<6, 6–12 and 13–18 years), and intervention type (physical activity, diet or both), setting (educational, family or both) and duration (≤1 or >1 year). The search was also extended to other databases. Hand‐searching techniques were also applied. The Cochrane 'risk of bias' was applied for quality assessment. Results: Seventy‐two studies were meta‐analysed. Overall, the best results were achieved by programmes combining diet and physical activity ( n  = 39). With regard to the setting, programmes involving both school and family and lasting ≤1 year were the most efficacious for 6‐ to 12‐year‐old children ( n  = 26); family‐based‐only interventions were also effective in children <6 years old ( n  = 2), although results have to be interpreted cautiously because of the small number of patients enrolled and the high study heterogeneity. In 13‐ to 18‐year‐old patients, interventions delivered at school ( n  = 8) were substantially unsuccessful. Conclusions: Interventions for childhood obesity prevention should include both diet and physical activity, be preferentially targeted towards school age children and involve both the school and family setting. However, because of the important methodological limitations associated with currently available literature, additional studies are needed to draw definite conclusions.